Lighting up silicon nanoparticles with Mie resonances - Chengyun Zhang (Nature Portfolio, 2018)
As an indirect semiconductor, silicon shows notoriously inefficient luminescence. Here, the authors utilize the Mie resonances in silicon nanoparticles to demonstrate visible white-light emission, both from free-standing spheres and particles etched on a silicon-on-insulator substrate.